Acid-sensing Ion Channel 3 Overexpression in Incisions Regulated by Nerve Growth Factor Participates in Postoperative Nociception in Rats. (December 2020) - Li, Hao; Li, Huiping; Cheng, Jing; Liu, Xicheng; Zhang, Zhongjun; Wu, Chaoran
Abstract : Background: Acid-sensing ion channel 3 (ASIC3) upregulation has been reported in dorsal root ganglion neurons after incision and contributes to postoperative nociception. This study hypothesized that upregulation of ASIC3 in incised tissues is induced by nerve growth factor through the phosphoinositide 3–kinase/protein kinase B signaling pathway. Methods: A plantar incision model was established in adult male and female Sprague–Dawley rats. ASIC3 was inhibited by APETx2 treatment, small interfering RNA treatment, or ASIC3 knockout. Sciatic nerve ligation was performed to analyze ASIC3 transport. A nerve growth factor antibody and a phosphoinositide 3–kinase inhibitor were used to investigate the mechanism by which nerve growth factor regulates ASIC3 expression. Results: Acid-sensing ion channel 3 inhibition decreased incisional guarding and mechanical nociception. ASIC3 protein levels were increased in skin and muscle 4 h after incision (mean ± SD: 5.4 ± 3.2-fold in skin, n = 6, P = 0.001; 4.3 ± 2.2-fold in muscle, n = 6, P = 0.001). Sciatic nerve ligation revealed bidirectional ASIC3 transport. Nerve growth factor antibody treatment inhibited the expression of ASIC3 (mean ± SD: antibody 2.3 ± 0.8-fold vs. vehicle 4.9 ± 2.4-fold, n = 6, P = 0.036) and phosphorylated protein kinase B (mean ± SD: antibody 0.8 ± 0.3-fold vs. vehicle 1.8 ± 0.8-fold, n = 6, P = 0.010) in incised tissues. Intraplantar injection of nerve growth factor increased the expression of ASIC3 and phosphorylated protein kinase B. ASIC3 expression and incisional pain–related behaviors were inhibited by pretreatment with the phosphoinositide 3–kinase inhibitor LY294002. Conclusions: Acid-sensing ion channel 3 overexpression in incisions contributes to postoperative guarding and mechanical nociception. Bidirectional transport of ASIC3 between incised tissues and dorsal root ganglion neurons occurs through the sciatic nerve. Nerve growth factor regulates ASIC3 expression after plantar incision through the phosphoinositide 3–kinase/protein kinase B signaling pathway. Abstract : Using a rat model of surgical incision, it was shown that both male and female animals demonstrated less wound area sensitization when acid-sensing ion channel 3 channels were pharmacologically blocked or knocked down using small interfering RNA. Anti–nerve growth factor treatment blocked the upregulation of acid-sensing ion channel 3 expression after incision and reduced the pain-related behaviors.